Bottom-up assembled synthetic SARS-CoV-2 miniviruses reveal lipid membrane affinity of omicron variant spike glycoprotein - Yagüe Relimpio, Ana; Fink, Andreas; Bui, Duc Thien; Fabritz, Sebastian; Schröter, Martin; Ruggieri, Alessia; Platzman, Ilia; Spatz, Joachim P. (ACS nano, 2023)
The ongoing COVID-19 pandemic has been brought on by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The spike glycoprotein (S), which decorates the viral envelope forming a corona, is responsible for the binding to the angiotensin-converting enzyme 2 (ACE2) receptor and initiating the infection. In comparison to previous variants, Omicron S presents additional binding sites as well as a more positive surface charge. These changes hint at additional molecular targets for interactions between virus and cell, such as the cell membrane or proteoglycans on the cell surface. Herein, bottom-up assembled synthetic SARS-CoV-2 miniviruses (MiniVs), with a lipid composition similar to that of infectious particles, are implemented to study and compare the binding properties of Omicron and Alpha variants. Toward this end, a systematic functional screening is performed to study the binding ability of Omicron and Alpha S proteins to ACE2-functionalized and nonfunctionalized planar supported lipid bilayers. Moreover, giant unilamellar vesicles are used as a cell membrane model to perform competitive interaction assays of the two variants. Finally, two cell lines with and without presentation of the ACE2 receptor are used to confirm the binding properties of the Omicron and Alpha MiniVs to the cellular membrane. Altogether, the results reveal a significantly higher affinity of Omicron S toward both the lipid membrane and ACE2 receptor. The research presented here highlights the advantages of creating and using bottom-up assembled SARS-CoV-2 viruses to understand the impact of changes in the affinity of S for ACE2 in infection studies.
Gesehen am 18.04.2024